Alcohol functionality in the fatty acid backbone of sphingomyelin guides the inhibition of blood coagulation. Issue 6 (15th January 2021) - Mallik, S.; Prasad, R.; Das, K.; Sen, P.
Abstract : Cell-surface sphingomyelin (SM) inhibits binary and ternary complex activity of blood coagulation. Abstract : Cell-surface sphingomyelin (SM) inhibits binary and ternary complex activity of blood coagulation by an unknown mechanism. Here we show the OH functionality of SM contributes in forming the close assembly through intermolecular H-bond and through Ca 2+ chelation, which restricts the protein–lipid/protein–protein interactions and thus inhibits the coagulation procedure.